2007
DOI: 10.1111/j.1744-7402.2007.02177.x
|View full text |Cite
|
Sign up to set email alerts
|

Wetting and Reaction Characteristics of Al2O3/SiC Composite Refractories by Molten Aluminum and Aluminum Alloy

Abstract: The reactive wetting behavior in molten aluminum and Al alloy was investigated by the sessile drop method for three alumina‐silicon carbide composites, namely TC, TQ, and MC. The initial contact angle for all the three refractory substrates was obtuse in spite of a gradual decrease with time in the first hour of the experiment. TC showed a higher contact angle than TQ and MC. The difference in wetting properties among these refractories is attributed to their compositional and microstructural variations. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The analysis shows presence of Mg, Al and O at the interface, indicating the formation of spinel MgAl2O4 at the interface that leads to good wetting and strong interface. The peroxidation process of SiC particles enhances the formation of SiO2 layer on the particles [21]. During the composite preparation, the SiO2 layer on the surfaces of SiC particles could react with Mg and Al in the matrix to form MgAl2O4 according to the following reactions [21] 2Mg + SiO2 = 2MgO + Si MgO + 4Al + 3SiO2 = 2MgAl2O4 + 3Si [21] Fig.…”
Section: Interface Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis shows presence of Mg, Al and O at the interface, indicating the formation of spinel MgAl2O4 at the interface that leads to good wetting and strong interface. The peroxidation process of SiC particles enhances the formation of SiO2 layer on the particles [21]. During the composite preparation, the SiO2 layer on the surfaces of SiC particles could react with Mg and Al in the matrix to form MgAl2O4 according to the following reactions [21] 2Mg + SiO2 = 2MgO + Si MgO + 4Al + 3SiO2 = 2MgAl2O4 + 3Si [21] Fig.…”
Section: Interface Characteristicsmentioning
confidence: 99%
“…The peroxidation process of SiC particles enhances the formation of SiO2 layer on the particles [21]. During the composite preparation, the SiO2 layer on the surfaces of SiC particles could react with Mg and Al in the matrix to form MgAl2O4 according to the following reactions [21] 2Mg + SiO2 = 2MgO + Si MgO + 4Al + 3SiO2 = 2MgAl2O4 + 3Si [21] Fig. 3 (a-f…”
Section: Interface Characteristicsmentioning
confidence: 99%
“…The most commonly used method is active brazing using metal interlayer. With the help of metal interlayer such as CuTi, CuZr, and AgCuTi, the alumina can be joined successfully to itself or metals. However, residual stress tends to generate in the joint due to the mismatch of the coefficient of thermal expansion between ceramic and AgCuTi, which severely degrades the quality of the joint.…”
Section: Introductionmentioning
confidence: 99%
“…The wetting is also strongly influenced by the alloying elements. It was shown that Mg promotes the wetting and lowers the wetting temperature . Additionally, the presence of Mg in the alloy can lead to the formation of the spinel phase MgAl 2 O 4 and this might promote the wetting even more .…”
Section: Introductionmentioning
confidence: 99%